2020
DOI: 10.1094/phyto-05-19-0156-r
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Diffusible Lipopeptides and Fungal Virulence Genes During Bacillus amyloliquefaciens EZ1509-Mediated Suppression of Sclerotinia sclerotiorum

Abstract: Sclerotinia sclerotiorum is a devastating necrotrophic pathogen that infects multiple crops, and its control is an unremitting challenge. In this work, we attempted to gain insights into the pivotal role of lipopeptides (LPs) in the antifungal activity of Bacillus amyloliquefaciens EZ1509. In a comparative study involving five Bacillus strains, B. amyloliquefaciens EZ1509 harboring four LPs biosynthetic genes (viz. surfactin, iturin, fengycin, and bacilysin) exhibited promising antifungal activity against S. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 73 publications
2
23
0
Order By: Relevance
“…Antibiosis is the main mechanism of biological control that has been well-studied genetically and biochemically [35]. In recent years, several studies have reported the inhibition of fungal pathogens by cyclic lipopeptides [6,37,38]. The excretion of antimicrobial compounds by Bacillus species is the primary cause of the formation of fungal growth inhibition zones in dual culture [39].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiosis is the main mechanism of biological control that has been well-studied genetically and biochemically [35]. In recent years, several studies have reported the inhibition of fungal pathogens by cyclic lipopeptides [6,37,38]. The excretion of antimicrobial compounds by Bacillus species is the primary cause of the formation of fungal growth inhibition zones in dual culture [39].…”
Section: Discussionmentioning
confidence: 99%
“…A mycelial plug of 0.6 cm from fungus grown for 4 days was patched in the center of PDA medium plates and 5 µL of each bacterial suspension with optical density (OD) of 2.50 (at 600 nm) was inoculated 3 cm away from the patched mycelium. Sterilized LB media was also used in the same plate as control [7]. The plates were incubated at 25 • C and 15 • C for 4 days to observe the fungal inhibition zone at optimal growth temperature as well as at cold conditions.…”
Section: Dual Culture Assay For Antagonismmentioning
confidence: 99%
“…are reported to be the most efficient biocontrol agents. These bacteria have the ability to survive and colonize complex environments and to produce a wide range of antifungal extracellular enzymes as well as antimicrobial secondary metabolites including lipopeptides (LPs) [6,7]. Bacillus can produce multiple low molecular-weight, amphiphilic, antimicrobial compounds synthesized by non-ribosomal peptide synthetase (NRPS) enzyme-complexes such as surfactin, iturins, and fengycin [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Among iturins, iturin A and C, bacillomycin D, F, L, LC, and mycosubtiline are the main variants of this chemical family that increase membrane permeability and therefore display strong antifungal activity [37]. This antifungal activity is based on the formation of pores in the fungal cell membranes that cause an osmotic imbalance, membrane disruption, and solubilization [51]. The antimicrobial effect of fengycin is high, especially against filamentous fungi [51], as this molecule interacts with the membrane lipid bilayer.…”
Section: Biocontrol Mechanisms Against S Sclerotiorum 101 Protection ...mentioning
confidence: 99%
“…This antifungal activity is based on the formation of pores in the fungal cell membranes that cause an osmotic imbalance, membrane disruption, and solubilization [51]. The antimicrobial effect of fengycin is high, especially against filamentous fungi [51], as this molecule interacts with the membrane lipid bilayer. It causes its solubilization, modifies its structure and permeability, and creates ion-conducting channels that pass through it [37,51].…”
Section: Biocontrol Mechanisms Against S Sclerotiorum 101 Protection ...mentioning
confidence: 99%